Bacterial community structure associated with smokeless tobacco reference products under different storage conditions and durations - Liu, Shuang; Greenhut, Isaac V.; Moe, Luke A. (Frontiers in Public Health, 2025)
The microbiology of smokeless tobacco products (STPs), such as moist snuff, snus, and loose-leaf chewing tobacco, has recently received significant interest owing to the impact of microbes on product storage and safety. Tobacco leaf-associated microbes, as well as microbes introduced during product manufacturing, may play a role in formation of carcinogenic nitrosamine compounds during manufacturing and product spoilage upon storage. The Center for Tobacco Reference Products at the University of Kentucky has, since 1968, provided tobacco reference products for non-clinical research purposes. These products, including cigarettes, cigars, and STPs, are commercially produced and meant to be representative of off-the-shelf products. Reference products provide the opportunity to enhance reproducibility and reduce batch-to-batch variability. In this study, the microbial communities of smokeless tobacco reference products 3S1 (loose-leaf chewing tobacco), 3S3 (moist snuff), 1S4 (Swedish-style snus), and 1S5 (American snus) were analyzed using culture-based and culture-independent analysis. Bacterial and fungal loads were assessed on three media types, and 16S rDNA amplicon sequencing was used to track the bacterial community structure as a function of time and product storage temperature. Culturable loads were consistently highest with moist snuff ( 106–107 CFU/g) and lowest with the snus products ( 102–103 CFU/g). Bacterial community structure varied according to product, with Firmicutes and Proteobacteria the primary phyla observed. At the genus level, the most commonly observed operational taxonomic units (OTUs) belonged to Tetragenococcus and Staphylococcus, but their relative abundances differed according to product. The moist snuff product showed the most significant shift in microbial community structure according to storage temperature, with an increase in Atopostipes, Staphylococcus, and Carnobacteriacea OTUs at room temperature and an increase in Lentibacillus at 37 °C. From these studies, we conclude that elevated storage temperatures will alter STP microbial communities but that storage at −20 °C is sufficient for long-term storage of the reference products.